2016
DOI: 10.17795/ccn-8124
|View full text |Cite
|
Sign up to set email alerts
|

Study of Fatigue and Associated Factors in Patients with Chronic Heart Failure

Abstract: Background: Many factors may be involved in fatigue of patients with chronic heart failure (CHF). Objectives: The present study was conducted to determine fatigue and associated factors in patients with heart failure. Methods:The present descriptive-analytical study was conducted on patients with CHF admitted to Imam Sajjad hospital of Ramsar in 2014. Data collection tools included: 1) multidimensional assessment of fatigue (MAF) scale, 2) the Pittsburgh sleep quality index (PSQI), 3) the hospital anxiety and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
1
5
1
1
Order By: Relevance
“…In this study, the more fatigue is perceived, the poorer the sleep quality experienced by participants, similar to the finding from the previous study by Nasiri et al (2016). Some studies also confirmed the associations of fatigue and global PSQI score using different kind of fatigue measurements (Dos Santos et al, 2011, Fink et al, 2012, Riegel, 2012.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In this study, the more fatigue is perceived, the poorer the sleep quality experienced by participants, similar to the finding from the previous study by Nasiri et al (2016). Some studies also confirmed the associations of fatigue and global PSQI score using different kind of fatigue measurements (Dos Santos et al, 2011, Fink et al, 2012, Riegel, 2012.…”
Section: Discussionsupporting
confidence: 90%
“…The participants in this study seemed to have a lower mean global fatigue index/GFI (22.99), ranging from 10 -44 on the MAF than several studies in USA (29.8 to 35.08) (Jeon and Redeker, 2016, Redeker et al, 2010b, Redeker et al, 2012, Fritschi and Redeker, 2015. Findings from another study by Nasiri et al (2016) revealed a lower score of GFI among patients with HF in Iran (5.92). This study also had different scores on the domains.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations